PRAGMATIC ANALYSIS OF FLOUTING MAXIM BY JUSTIN TIFFANI IN PWK PODCAST A STUDY OF ANOMALY IN DIGITAL HUMOR - Luis Aditya Ramadhan (Linguistik : Jurnal Bahasa dan Sastra, 2026)
This study aims to identify and describe the types of maximum violations committed by Dustin Tiffani in the  Praz Warung Kopi (PWK) podcast program on the Has Kreatif YouTube channel. Dustin Tiffani is known for having a unique speaking style that is often considered to jump over common logic, which in pragmatic studies is categorized as a violation of the principle of cooperation. The method used in this study is descriptive qualitative with content analysis techniques. Data were collected through the technique of listening and recording the transcripts of conversations, then analyzed using Grice's (1975) maximal theory and Leech's (1983) principle of politeness. The results of the study show that there are 10 significant data on maximum violations which include maximum quantity, quality, relevance, manners, and politeness. Violations of the maxim of relevance and maxim of means became the most dominant finding, where the subject often gave incoherent responses and used ambiguous sentence structures. These scientific findings show that in the digital entertainment ecosystem, maximal violations do not lead to communication failures, but rather serve as a means to construct humorous implications through cognitive incongruity.